(untitled) (Global Journal of Medical Research, 2023)
Introduction Due to its high mortality rate it is necessary to discuss and understand the aspects surrounding atherosclerotic diseases including the current role of revascularization in a large number of cases Additionally it is necessary to discuss the aging process in women and the effects of hormonal changes Methodology This is a literature review with a search in databases using 60 scientific articles as a basis and being filtered based on scientific impact and approach